Monitoring Cirrus Cloud and Tropopause Height over Hanoi Using a Compact Lidar System - Hai, Bui Van; Trung, Dinh Van; Tuan, Nguyen Xuan; Thang, Dao Duy; Binh, Nguyen Thanh (Communications in Physics, 2013)
Abstract. Cirrus clouds in the upper troposphere and the lower stratosphere have attracted great attention due to their important role and impact on the atmospheric radioactive balance. Because cirrus clouds are located high in the atmosphere, their study requires a high resolution remote sensing technique not only for detection but also for the characterization of their properties. The lidar technique with its inherent high sensitivity and resolution has become an indispensible tool for studying and improving our understanding of cirrus cloud. Using lidar technique we can simultaneously measure the cloud height, thickness and follow its temporal evolution. In this paper we describe the development of a compact and highly sensitive lidar system with the aim to remotely monitor for the first time the cirrus clouds over Hanoi (21001’42’’N, 105051’12’’W). From the lidar data collected during the year 2011. We derive the mean cloud height, location of cloud top, the cloud mean thickness and their temporal evolution. We then compare the location of the cloud top with the position of the tropopause determined the radiosonde data and found good that the distance between cloud top and tropopause remains fairly stable, indicating that generally the top of cirrus clouds is the good tracer of the tropopause. We found that the cirrus clouds are generally located at height between 11.2 to 15 km with average height of 13.4 km. Their thickness is between 0.3 and 3.8 km with average value of 1.7 km. We also compare the properties of cirrus cloud with that observed at other locations around the world based on lidar technique.